Sensitivity to Thyroid Hormone Indices Are Closely Associated With NAFLD - Lai, Shuiqing; Li, Jiarong; Wang, Zixiao; Wang, Wei; Guan, Haixia (Frontiers in Endocrinology, 2021)
Background Previous studies on the association between thyroid function and non‐alcoholic fatty liver disease (NAFLD) have contradicted. Acquired resistance to thyroid hormone theory might provide a reasonable explanation for these contradictions. We aimed to analyze the association between sensitivity to thyroid hormone indices with NAFLD. Methods A total of 4,610 individuals from the health medical center of the First Hospital of China Medical University were included in this study. The previously used thyroid feedback quantile-based index (TFQIFT4) was calculated. Also, we substituted free triiodothyronine (FT3) into the TFQI formulas to get the TFQIFT3 index. NAFLD was defined using abdominal ultrasound. Results Study results showed that FT3/FT4 and TFQIFT3 were positively correlated with the triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels (P<0.05) and negatively correlated with high-density lipoprotein cholesterol (HDL-C) level (P<0.05). In contrast, TFQIFT4 was positively correlated with HDL-C level (P < 0.05). After adjustment for multiple confounders, FT3, FT3/FT4, and TFQIFT3 were positively associated with the risks of dyslipidemia and NAFLD (P < 0.05). TFQIFT3 and FT3/FT4 performed better than TFQIFT4 on ROC analyses for NAFLD prediction, although the diagnostic sensitivity and specificity at the optimal cut-points were low. However, no association was observed between TFQIFT4 with the risks of dyslipidemia and NAFLD. Conclusion TFQIFT3 and FT3/FT4 can be used as new indicators for predicting dyslipidemia and NAFLD, although with low sensitivity and specificity at the optimal cut-points, while TFQIFT4 has insufficient evidence in predicting dyslipidemia and NAFLD.